1982
DOI: 10.1073/pnas.79.21.6541
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids and phorbol esters alter release of fibronectin from enucleated cells.

Abstract: Addition of 12-tetradecanoylphorbol 13-acetate (TPA) to cultures of intact Swiss mouse 3T3 fibroblasts induced a dose-dependent increase in ornithine decarboxylase (OrnDCase) activity. Over the same concentration range, 10-9 to 10-6 M, TPA induced the release of radioactively labeled fibronectin (FN) from the cells into the culture medium. Retinoic acid, a derivative of vitamin A, inhibited in a dose-dependent manner both the increase in OrnDCase activity and the release of FN induced by TPA. To examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The mechanisms of the actions of retinoic acid and its parent, retinol, appear to be nuclear (21,22) as well as extranuclear (23). In the present studies we have shown that retinoic acid, but not retinol, is a "calmodulin antagonist" in the context of the activation of human red cell Ca2+-ATPase by calmodulin.…”
Section: Discussionmentioning
confidence: 53%
“…The mechanisms of the actions of retinoic acid and its parent, retinol, appear to be nuclear (21,22) as well as extranuclear (23). In the present studies we have shown that retinoic acid, but not retinol, is a "calmodulin antagonist" in the context of the activation of human red cell Ca2+-ATPase by calmodulin.…”
Section: Discussionmentioning
confidence: 53%
“…The retinoids exert profound effects on development and differentiation in a wide variety of systems (1)(2)(3)(4)(5)(6)(7). In the developing chick limb, retinoic acid has the ability to change the positional information of cells in a very precise manner: for example, application of retinoic acid to the side opposite the zone of polarizing activity causes digit pattern duplication (8,9).…”
mentioning
confidence: 99%
“…5) Although protein kinase C appears to be involved in these responses, the mechanism by which they are affected is not identical. ODCase induction involves a nuclear event, whereas reduction of EGF binding does not (5)(6)(7)17). We hypothesize that activation of protein kinase C transmits a signal to the nucleus, which results in enhanced transcription of the ODCase gene and increased ODCase synthesis.…”
mentioning
confidence: 99%
“…A strong correlation exists between the induction of ODCase and the promotion of tumor formation (4,(12)(13)(14)(15)(16). Unlike the inhibition of EGF binding (5)(6)(7)(8), ODCase induction requires nuclear events (17).…”
mentioning
confidence: 99%